The Effects of Prior Victimization on Delinquency Type among Justice-Involved Youths. Issue 6 (18th August 2021) - Cain, Calli M.
ABSTRACT: Youth with a history of victimization have an increased risk of delinquency and justice system involvement throughout the life-course but the nature of this relationship is imprecise. This study uses a nationally representative sample of incarcerated youth to examine whether youth with a history of victimization are involved in the justice system for different offenses than non-victimized youth, and the relationship between victimization types (and polyvicitmzation) and offense types. Results indicate that victimized youth were more likely to be system involved for violent offenses, while youths without a history of victimization were more likely to be involved for minor, non-violent offenses.